2000
DOI: 10.1021/ja0011865
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of DNA Topology in Reactions between Plasmid DNA and Cationic Copolymers

Abstract: This study for the first time demonstrates phenomenon of recognition of DNA tertiary structure by the synthetic polycationic molecules. Effects of DNA topology were evaluated using supercoiled and linearized forms of plasmid DNA (scDNA and lDNA). Recognition is achieved by using relatively simple chemical structures interacting with the DNA. Two polycations modified with water-soluble poly(ethylene glycol) (PEG) chains, PEG−block−poly(N-methyl-4-vinylpyridinium sulfate) (PEG−b−PVP) and PEG−graft−polyethyleneim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
150
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(159 citation statements)
references
References 15 publications
(19 reference statements)
9
150
0
Order By: Relevance
“…After intravenous administration of naked DNA, most of the DNA was degraded into small fragments within 5 min and was seen as smears. This is in line with an observation reported by Lew et al 30 On the other hand, PIC micelles with charge ratios of 1:4 and PLL length of 48 mer showed longer retention time in the blood as supercoiled DNA (30 min 32 also reported that complexes of block copolymers with supercoiled DNA are more susceptible to make complex with block cationomer than linear DNA, suggesting supercoiled DNA to form polyplex with higher stability than linear DNA. 32 On the other hand, in our study, most complexed DNA molecules are in the supercoiled state at the beginning, being subjected to gradual attack by plasma nuclease during blood circulation converted into open circular and subsequently into linear form.…”
Section: Gene Therapysupporting
confidence: 91%
See 1 more Smart Citation
“…After intravenous administration of naked DNA, most of the DNA was degraded into small fragments within 5 min and was seen as smears. This is in line with an observation reported by Lew et al 30 On the other hand, PIC micelles with charge ratios of 1:4 and PLL length of 48 mer showed longer retention time in the blood as supercoiled DNA (30 min 32 also reported that complexes of block copolymers with supercoiled DNA are more susceptible to make complex with block cationomer than linear DNA, suggesting supercoiled DNA to form polyplex with higher stability than linear DNA. 32 On the other hand, in our study, most complexed DNA molecules are in the supercoiled state at the beginning, being subjected to gradual attack by plasma nuclease during blood circulation converted into open circular and subsequently into linear form.…”
Section: Gene Therapysupporting
confidence: 91%
“…Thus, eventually, a fraction of linear DNA accumulates in time-dependent manner. This may be a reason for the apparent increase of linear DNA in the blood sample collected in the later time period, and is not necessarily inconsistent with observation by Ward et al 31 and Bronich et al 32 No small fragments of DNA were observed in any of the samples, suggesting that DNA in the PIC micelles is nuclease resistant in the blood. The results are in good agreement with the in vitro data previously described which showed resistance of PIC micelles to Dnase I.…”
Section: Gene Therapysupporting
confidence: 75%
“…C3Ms can be formed from virtually any combination of oppositely charged species, provided at least one of the species carries one or several solvophilic units that remain soluble upon complexation. By far the most studied are combinations including a diblock copolymer to stabilise the complex, while combinations with random [14] and graft [15] copolymers are relatively little reported on. Recent examples include C3Ms consisting of a copolymer and DNA [15,16], RNA [17], enzymes [5], homopolymer [10], dendrimer [3], drug [3], surfactant [14], metal ion [18,19], or coordination polymer [20].…”
Section: Introductionmentioning
confidence: 99%
“…By far the most studied are combinations including a diblock copolymer to stabilise the complex, while combinations with random [14] and graft [15] copolymers are relatively little reported on. Recent examples include C3Ms consisting of a copolymer and DNA [15,16], RNA [17], enzymes [5], homopolymer [10], dendrimer [3], drug [3], surfactant [14], metal ion [18,19], or coordination polymer [20]. Their potential as novel drug carrier systems, encapsulating for example DNA, RNA, enzymes, and drugs has widely been investigated [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…[28] The ability of the copolymer to bind to DNA was monitored by recording the fluorescence of EB-DNA complex. [29] The addition of cationic liposomes which are able to displace EB from the EB-DNA complex results in the quenching of the fluorescence.…”
Section: Eb Quenching Experimentsmentioning
confidence: 99%